PERKEMBANGAN PERUMAHAN DAN DIVERSIFIKASI MATA PENCAHARIAN PENDUDUK KECAMATAN UNGARAN BARAT DAN UNGARAN TIMUR (Faculty of Social Science, Universitas Negeri Semarang, 2012)
This research aims to study the development of housing and livelihood diversification, population located in the Subdistrict of West and East Ungaran. The methods used to analyze the housing development process approach is use to analyze the spatial pattern of housing, with the nearest neighbor analysis, and to study the livelihood diversification using descriptive analysis. Based on these studies, the housing in the two districts ranging from 1986 until the year 2009 experienced a very rapid development, from the original only in one location in a village into 37 unit with locations spread over 12 village/town. Settlement patterns in the two districts are spread that attempted by the numbers of 2.59 and 1, 73. The livelihood of most of the population is non agriculture and only 10 percent whose livelihoods in agriculture. All household livelihood to diversify to meet the necessities of life.